Sexual Offences Courts in South Africa: quo vadis? - Kruger, H. B.; Reyneke, J. M. (Faculty of Law, University of the Free State, 2008)
Since the establishment of the first Sexual Offences Court in Wynberg in 1993, various developments have taken place that include, but are not limited to, the following : several investigations into these courts were undertaken; the Sexual Offences and Community Affairs Unit (SOCA Unit) was established; a blueprint for Sexual Offences Courts was drafted and later refined; and, by 2007, the number of Sexual Offences Courts had increased to 59. These courts have performed exceptionally well compared with general regional courts and conviction rates rose to 70 per cent on average. Despite the obvious success of these courts, the Minister of Justice and Constitutional Development declared a moratorium on the establishment of additional Sexual Offences Courts pending the outcome of an evaluation of existing Sexual Offences Courts. In this article, a synopsis of the development of Sexual Offences Courts is given and the subsequent evaluation commissioned by the Minister is assessed and is supplemented with recommendations to enhance efforts to combat sexual offences through the Sexual Offences Courts.

Sedert die totstandkoming van die eerste Howe vir Seksuele Misdrywe in 1993 te Wynberg het verskeie ontwikkelinge plaasgevind, onder andere is verskeie ondersoeke geloods, die Sexual Offences and Community Affairs Unit (SOCA Unit) is gestig, 'n bloudruk vir Howe vir Seksuele Misdrywe is opgestel en later verfyn en teen 2007 was daar 59 Howe vir Seksuele Misdrywe operasioneel. Hierdie howe het besonder goed gevaar in vergelyking met gewone streekshowe en die skuldigbevindingskoers in hierdie howe het gestyg tot gemiddeld 70 persent. Ten spyte van die ooglopende sukses van hierdie howe het die Minister van Justisie en Grondwetlike Ontwikkeling 'n moratorium geplaas op die vestiging van verdere Howe vir Seksuele Misdrywe hangende die uitkoms van 'n evaluering van die bestaande Howe vir Seksuele Misdrywe. In hierdie artikel word die ontwikkeling van die Howe vir Seksuele Misdrywe saamgevat en die resultate van die assessering wat die Minister aangevra het word geëvalueer en aanbevelings word gemaak om die bekamping van seksuele misdrywe in die Howe vir Seksuele Misdrywe te versterk.